High-reliability emergency response teams in the hospital: improving quality and safety using in situ simulation training. Issue 6 (1st March 2013) - Wheeler, Derek S; Geis, Gary; Mack, Elizabeth H; LeMaster, Tom; Patterson, Mary D
Abstract : Introduction: In situ simulation training is a team-based training technique conducted on actual patient care units using equipment and resources from that unit, and involving actual members of the healthcare team. We describe our experience with in situ simulation training in a major children's medical centre. Materials and methods: In situ simulations were conducted using standardised scenarios approximately twice per month on inpatient hospital units on a rotating basis. Simulations were scheduled so that each unit participated in at least two in situ simulations per year. Simulations were conducted on a revolving schedule alternating on the day and night shifts and were unannounced. Scenarios were preselected to maximise the educational experience, and frequently involved clinical deterioration to cardiopulmonary arrest. Results: We performed 64 of the scheduled 112 (57%) in situ simulations on all shifts and all units over 21 months. We identified 134 latent safety threats and knowledge gaps during these in situ simulations, which we categorised as medication, equipment, and/or resource/system threats. Identification of these errors resulted in modification of systems to reduce the risk of error. In situ simulations also provided a method to reinforce teamwork behaviours, such as the use of assertive statements, role clarity, performance of frequent updating, development of a shared mental model, performance of independent double checks of high-risk medicines, and overcoming authority gradients between team members. Participants stated that the training programme was effective and did not disrupt patient care. Conclusions: In situ simulations can identify latent safety threats, identify knowledge gaps, and reinforce teamwork behaviours when used as part of an organisation-wide safety programme.